2021
DOI: 10.1177/26349795211007092
|View full text |Cite
|
Sign up to set email alerts
|

Guardian of the Snacks: Toward designing a companion for mindful snacking

Abstract: COVID-19 has brought significant changes to our lives and eating practices, where many of us are required to not only stay at home but also eat at home. This is particularly challenging for lone-person households as eating alone can be boring, less motivating and could lead to unhealthy behaviors such as mindless snacking or skipping of meals. To remedy such situations, we present Guardian of the Snacks, a tangible multimodal system that encourages mindful snacking by offering a playful companionship to snacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…For people who live alone, such as many older people, prototypes of technological systems are being proposed to enable socialization with others during meals, as demonstrated by Korsgaard et al [ 30 ]. In situations with no interactions with other humans, the company of technology was a distraction as well as a form of entertainment while eating alone [ 77 ] that influences the time spent eating, the amount of food ingested, and the food choice itself [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…For people who live alone, such as many older people, prototypes of technological systems are being proposed to enable socialization with others during meals, as demonstrated by Korsgaard et al [ 30 ]. In situations with no interactions with other humans, the company of technology was a distraction as well as a form of entertainment while eating alone [ 77 ] that influences the time spent eating, the amount of food ingested, and the food choice itself [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we would like to point out to technology with the purpose of behavior change, which seems to have potential through nutrition tracking ( Casas et al, 2018 ) or nudging ( Bomfim et al, 2020 ; Khot et al, 2021 ), but rarely found relevance in the everyday life of our participants. The exception to this is in tracking the shopping expenditures of some participants.…”
Section: Discussionmentioning
confidence: 99%
“…Digital commensality encompasses technology usage to fulfill social needs for companionship during mealtime. The idea is to connect remote diners or use screen-based media, digital pets, or robots ( Khot et al, 2021 ; Spence et al, 2019 ). An example of remote dining, or virtual co-dining, is provided by approaches such as the Telematic Dinner Party , where cameras and projections not only connect dinner guests across different locations but also make their table activities visible (e.g., cutlery movements) ( Barden et al, 2012 ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In methods too, contributions have conducted explorations of synergies, as with digital humanities on distant viewing (Hiippala, 2021). Synergies have been established with other domains and professions, such as explorations of light in architecture (Lowings, 2021) and product design in human-computer interaction (Khot et al, 2021), which shows applications of multimodal research for everyday needs such as facilitating healthy relations with snacking. New fields have been launched or mapped further, particularly through the journal special issues, such as Multimodal anthropology (special issue 1.3) with papers on memory, senses, feminism and urbanism, migration, and the colonial gaze, as well as multimodality and race (special issue 3.3), while in volume 4, the special issue will map and consolidate further the application of multimodality in museums.…”
Section: Innovative Multimodal Research and Exploring The Potentials ...mentioning
confidence: 99%